Physical properties of the XScH3 (X: Ca, and Mg) perovskite hydrides and their hydrogen storage applications - Masood, M. Kashif; Khan, Wahidullah; Bibi, Shumaila; Kanwal, Anza; Bibi, Shazia; Noor, Gulab; A. Alothman, Asma; Rehman, Javed; Shafiee, Saiful 'Arifin (Elsevier Ltd., 2024)
We conducted a comprehensive investigation into the structural, mechanical, electronic, magnetic, thermodynamic, optical, and hydrogen storage properties of the novel XScH3 (X: Ca and Mg) perovskite hydrides by using density functional theory (DFT). Our calculations of the cohesive energy and elastic constants demonstrated that XScH3 compounds exhibit both thermal and mechanical stability. The metallic nature of current materials is based on the investigation of the electronic band structure and total density states. The analysis of Pugh’s ratio (B/G) indicated that these hydrides were ductile materials. Furthermore, it was found that their bonding type was primarily ionic. These substances have been classified as conductors with antiferromagnetic qualities in terms of their magnetic properties. Furthermore, these materials exhibited promising effects on optical properties such as conductivity, absorption, dielectric function, and refractive index. Our predictions revealed that CaScH3 was found to be optically superior hydride. The dynamic stability of these crystals was assessed by analyzing their phonon dispersion curves and by molecular dynamics simulations. Additionally, we studied their thermal properties, including heat capacity, entropy, energy, and free energy, as functions of temperature. Furthermore, our study investigated the hydrogen storage capacity of XScH3 compounds, with CaScH3 and MgScH3, demonstrating hydrogen storage capacities of 3.43 wt% and 4.18 wt%, respectively. This study marks the first exploration of XScH3 perovskite hydrides and offers new options for hydrogen storage materials.